The Effect of Music on Anxiety and Cardiovascular Indices in Patients Undergoing Coronary Artery Bypass Graft: A Randomized Controlled Trial - Heidari; Babaii; Abbasinia; Shamali; Abbasi; Rezaei (Kashan University of Medical Sciences, 2015)
Background The instability of cardiovascular indices and anxiety disorders are common among patients undergoing coronary artery bypass graft (CABG) and could interfere with their recovery. Therefore, improving the cardiovascular indices and anxiety is essential. Objectives This study aimed to investigate the effect of music therapy on anxiety and cardiovascular indices in patients undergoing CABG. Patients and Methods In this randomized controlled trial, 60 patients hospitalized in the cardiovascular surgical intensive care unit of Shahid Beheshti Hospital in Qom city, Iran, in 2013 were selected using a consecutive sampling method and randomly allocated into the experimental and control groups. In the experimental group, patients received 30 minutes of light music, whereas in the control group, patients had 30 minutes of rest in bed. The cardiovascular indices and anxiety were measured immediately before, immediately after and half an hour after the study. Data were analyzed using the chi-square test and repeated measures analysis of variance. Results Compared to the immediately before intervention, the mean anxiety scores immediately after and 30 minutes after the intervention were significantly lower in the experimental group (P < 0.037) while it did not significantly change in the control group. However, there were no significant differences regarding the cardiovascular indices in the three consecutive measurements (P > 0.05). Conclusions Music therapy is effective in decreasing anxiety among patients undergoing CABG. However, the intervention was not effective on cardiovascular indices. Music can effectively be used as a non-pharmacological method to manage anxiety after CABG.